The Global Research of Artificial Intelligence on Prostate Cancer: A 22-Year Bibliometric Analysis - Shen, Zefeng; Wu, Haiyang; Chen, Zeshi; Hu, Jintao; Pan, Jiexin; Kong, Jianqiu; Lin, Tianxin (Frontiers in Oncology, 2022)
Background：With the rapid development of technology, artificial intelligence has been widely used in the diagnosis and prognosis prediction of a variety of diseases, including prostate cancer. Facts have proved that AI has broad prospects in the accurate diagnosis and treatment of prostate cancer. Objective: This study mainly summarizes the research on the application of artificial intelligence in the field of prostate cancer through bibliometric analysis, and explores possible future research hotspots. Methods: The articles and reviews regarding application of AI in prostate cancer between 1999 and 2020 were selected from Web of Science Core Collection on August 23, 2021. Microsoft Excel 2019 and GraphPad Prism 8 were applied to analyze the targeted variables. VOSviewer (version 1.6.16), Citespace (version 5.8.R2) and a widely used online bibliometric platform were used to conduct co-authorship, co-citation, and co-occurrence analysis of countries, institutions, authors, references and keywords in this field. Results: A total of 2749 articles were selected in this study. AI-related research on prostate cancer increased exponentially in recent years, of which the United States was the most productive country with 1342 publications, and had close cooperation with many countries. The most productive institution and researcher were Henry Ford health system and Tewari Ashutosh K. However, the cooperation among most institutions or researchers was not close even if the high research outputs. The result of keyword analysis could divide all studies into three clusters: "Diagnosis and Prediction AI-related study", "Non-surgical AI-related study", "Surgery AI-related study". Meanwhile, the current research hotspots were "deep learning" and "multiparametric MRI". Conclusions: Artificial intelligence has broad application prospects in prostate cancer, and a growing number of scholars are devoted to AI-related research on prostate cancer. Meanwhile, the cooperation among various countries and institutions needs to be strengthened in the future. It can be projected that non-invasive diagnosis and accurate minimally invasive treatment through deep learning technology will still be the research focus in the next few years.